Physical and functional effects after an Immersive Virtual Reality based exercise program: experience in a Spanish Association of Parkinson's patients - Pablo Campo-Prieto; Diego Santos-García; José María Cancela-Carral; Gustavo Rodríguez-Fuentes (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2024)
Introduction: Physical exercise is an emerging approach in Parkinson's disease (PD) and new technologies such as immersive virtual reality (IVR) could contribute towards the development of specific programs targeting prevalent symptoms.